The Emerging Fish Pathogen Flavobacterium spartansii Isolated from Chinook Salmon: Comparative Genome Analysis and Molecular Manipulation - Chen, Shicheng; Blom, Jochen; Loch, Thomas P.; Faisal, Mohamed; Walker, Edward D. (Frontiers in Microbiology, 2017)
Flavobacterium spartansii strain T16T was isolated from a disease outbreak in hatchery-reared Chinook salmon (Oncorhynchus tshawytscha) fingerlings. To gain insight into its genomic content, structure and virulence pathogenesis factors, comparative genome analyses were performed using genomes from environmental and virulent Flavobacterium strains. F. spartansii shared low average nucleotide identity (ANI) to well-known fish-pathogenic flavobacteria (e.g., F. columnare, F. psychrophilum, and F. branchiophilum), indicating that it is a new and emerging fish pathogen. The genome in T16T had a length of 5,359,952 bp, a GC-content 35.7%, and 4,422 predicted protein-coding sequences. Flavobacterium core genome analysis showed that the number of shared genes decreased with the addition of input genomes and converged at 1182 genes. At least 8 genomic islands and 5 prophages were predicted in T16T. At least 133 virulence factors associated with virulence in pathogenic bacteria were highly conserved in F. spartansii T16T. Furthermore, genes linked to virulence in other bacterial species (e.g., those encoding for a type IX secretion system, collagenase and hemolysin) were found in the genome of F. spartansii T16T and were conserved in most of the analyzed pathogenic Flavobacterium. F. spartansii was resistant to ampicillin and penicillin, consistent with the presence of multiple genes encoding diverse lactamases and the penicillin-binding protein in the genome. To allow for future investigations into F. spartansii virulence in vivo, a transposon-based random mutagenesis strategy was attempted in F. spartansii T16T using pHimarEm1. Four putative gliding motility deficient mutants were obtained and the insertion sites of pHimarEm1 in the genome of these mutants were characterized. In total, study results clarify some of the mechanisms by which emerging flavobacterial fish pathogens may cause disease and also provide direly needed tools to investigate their pathogenesis.